PEMERIKSAAN OBJEK PAJAK PENGHASILAN MELALUI PENGUJIAN POS NERACA - Suwadi, Suwadi - (Simposium Nasional Keuangan Negara, 2020)
Basically, taxpayers are reluctant to pay income tax. Most tax auditors carry out audit on income tax through testing elements of Annual Income Tax Return (AITR). The value of AITR, that is obtained from income statement, has been adjusted by taxpayers. Thus, value of income statement is very closely related to balance sheet. The purpose of this research is to determine whether audit of income tax object through testing assets and liabilities reported on balance sheet can produce correction value. The method in this research is descriptive quantitative. In line with the concept of income both according to accounting and taxation, audit of income tax object through testing assets and liabilities reported on balance sheet can produce correction if based on the test result it turns out that assets balance are reported too low and/or liabilities balance are reported too high on balance sheet by taxpayers. This will have an impact on commercial net income reported too low so that Income Tax object reported is too low. However, technically there is still a different understanding.